Labour Market and Labour Market Policies During the Great Recession: The Case of Estonia - Raul Eamets (Institute for the Study of Labor (IZA), 2013)
The purpose of the paper is to analyse how labour market and labour market institutions reacted during recent crises. In early 1990s Estonia introduced a set of rather unique policy options like currency board as a ground for monetary policy, low taxes, open foreign trade policy, low public sector debts, annually balanced state budget etc. These measures caused very limited options to implement both monetary and fiscal policy. Macroeconomic adjustment will take place in such situation through the labour market. In the case of Estonia, we can observe a very high labour market flexibility, which played a crucial role in recent economic recession. The measures taken included a reduction of nominal wages, working hours and redundancies among employees. This indicates that the traditional institutional factors that protect workers and also could decrease the flexibility of the labour market, such as labour market regulation, social protection and union activities, are not very well developed in Estonia and do not have a significant effect on the outcomes of the labour market. The labour market reform was launched in Estonia in 2009. The main idea of the New Employment contract was that the termination of employment relations became less expensive for employers. Although empirical evidence show that the Employment Contracts Act entered into force at a time when most lay-offs had already been effected.
Keywords: J08; J21; J50; J63; 330; labour policy; Estonian labour market; labour market flexibility; labour market and recession; Arbeitsmarktpolitik; Arbeitsmarktflexibilität; Arbeitsbeziehungen; Wirtschaftskrise; Estland